Potensi Ketersediaan Air Pada Free Intake Wae Musur 1 dan 2 Untuk Pengembangan Lahan Pertanian Di DAS Borong Kabupaten Manggarai Timur - Simson ; Khaerudin , Dian Noorvy; Sulistyani, Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
This study aims to analyze the potential of water availability in the free intake of Wae Musur 1 and 2 which are used to meet the needs of functional and potential irrigation water in the Borong watershed, East Manggarai Regency. The method used in this research is quantitative analysis method. The calculated availability of water is surface water in the form of a reliable river discharge. Water requirements for functional and potential land are calculated based on the assumption that 1 hectare is equal to 1 liter / second. The analysis shows that the average availability of mainstay debit in January to December is 4,5 million m3/month. Balance sheet analysis shows that the mainstay discharge available for free intake of Wae Musur 1 and 2 is able to meet the needs of functional land irrigation water and is still surplus. Therefore, this surplus is used to meet potential land irrigation water needs. After analyzing the water balance, the potential for irrigation water needs is apparently still experiencing a surplus as well. Surplus ranges from 0,3 million to 6,3 million m3/month.